1988
DOI: 10.1007/bf02431532
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of non-opioid analgesia in intruder mice by selective neuronal and non-neuronal benzodiazepine recognition site ligands

Abstract: In male mice, the biologically significant experience of social defeat is associated with an acute non-opioid form of analgesia. Recent studies have shown that this reaction is sensitive to certain benzodiazepine receptor ligands but is unaffected by others. The present experiments were designed to assess the possibility that activity at "non-neuronal" benzodiazepine binding sites might account for this unusual pharmacological profile. Our results show that defeat analgesia was blocked by clonazepam (0.06-3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…3; Miczek et al 1985). In addition to the naloxone-reversible defeat stress-induced analgesia, a modest level of antinociception results from exposure to mild and short attacks by an opponent, and this type of antinociceptive response does not appear to be opioid-mediated since naloxone does not reverse this effect (Rodgers and Randall 1988). …”
Section: Introductionmentioning
confidence: 99%
“…3; Miczek et al 1985). In addition to the naloxone-reversible defeat stress-induced analgesia, a modest level of antinociception results from exposure to mild and short attacks by an opponent, and this type of antinociceptive response does not appear to be opioid-mediated since naloxone does not reverse this effect (Rodgers and Randall 1988). …”
Section: Introductionmentioning
confidence: 99%
“…A more ethological approach to the study ofbenzodiazepine administration and the blockage of analgesia has been reported by Rodgers and Randall (1987a, 1987b, 1988a, 1988b. These experimenters administered benzodiazepines during resident-intruder sessions and tested for analgesia both before and after such sessions.…”
Section: Methodsmentioning
confidence: 99%